Store-independent modulation of Ca(2+) entry through Orai by Septin 7 - Deb, Bipan Kumar (Nat Commun, 2016)
Orai channels are required for store-operated Ca(2+) entry (SOCE) in multiple cell types. Septins are a class of GTP-binding proteins that function as diffusion barriers in cells. Here we show that Septin 7 acts as a ‘molecular brake’ on activation of Orai channels in Drosophila neurons. Lowering Septin 7 levels results in dOrai-mediated Ca(2+) entry and higher cytosolic Ca(2+) in resting neurons. This Ca(2+) entry is independent of depletion of endoplasmic reticulum Ca(2+) stores and Ca(2+) release through the inositol-1,4,5-trisphosphate receptor. Importantly, store-independent Ca(2+) entry through Orai compensates for reduced SOCE in the Drosophila flight circuit. Moreover, overexpression of Septin 7 reduces both SOCE and flight duration, supporting its role as a negative regulator of Orai channel function in vivo. Septin 7 levels in neurons can, therefore, alter neural circuit function by modulating Orai function and Ca(2+) homeostasis.